Empathy in the design of assistive devices for older adults: An exploratory study with Portuguese women - Silva, Daniela (2022)
Assistive Devices (AD) aim to enhance the autonomy of their users, among whom are older adults. However, older adults often have negative feelings towards these products, such as the fear of dependence, which in turn influence their acceptance and use. These feelings can result from the use of design approaches that focus merely on users’ physical abilities. This article argues for the importance of rethinking approaches to the design of AD by focusing on a holistic and empathic view of older people. It also seeks to contribute to a richer understanding of what independence and dependence means to older people. This article describes an exploratory study with eleven older women, living in two distinct contexts in the north of Portugal – rural and urban. The qualitative data that emerged from this research were used to develop five empirical personas, to provide a readily usable and useful tool for design.